NORMALISASI PASAR KEPANDEAN KOTA SERANG MENUJU EKONOMI MAJU DI KOTA SERANG TAHUN 2026 - Dharmawan, Awan; Rosidin, Angga; Habib Alra'zie, Zakaria (Universitas Teknologi Surabaya, 2025)
This research aims to analyze the normalization of the Kepandean Market in Serang City and its impact on advancing the urban economy. The Kepandean Market, a vital economic center, has faced challenges related to infrastructure, spatial planning, and vendor management, which have hindered its potential. This study employs a qualitative descriptive method, collecting data through observation, in-depth interviews with traders and the market management, and documentation. The findings indicate that normalization efforts, including infrastructure revitalization, vendor relocation, and improved management, have significantly enhanced the market's functionality and aesthetics. These changes have led to an increase in visitor numbers, improved transaction volumes, and a more orderly trading environment. The implication of this normalization is a positive stimulus for the local economy, creating a multiplier effect that supports the vision of an advanced Serang City economy. This study concludes that a structured and well-managed market normalization is a key strategy for urban economic development.